An overview of asthma and airway hyper-responsiveness in Olympic athletes - Fitch, K. D. (British Journal of Sports Medicine, 2012)
Data from the past five Olympic Games obtained from athletes seeking to inhale ?2 adrenoceptor agonists (IBA) have identified those athletes with documented asthma and airway hyper-responsiveness (AHR). With a prevalence of about 8%, asthma/AHR is the commonest chronic medical condition experienced by Olympic athletes. In Summer and Winter athletes, there is a marked preponderance of asthma/AHR in endurance-trained athletes. The relatively late onset of asthma/AHR in many older athletes is suggestive that years of endurance training may be a contributory cause. Inspiring polluted or cold air is considered a significant aetiological factor in some but not all sports. During the last five Olympic Games, there has been improved management of athletes with asthma/AHR with a much higher proportion of athletes combining inhaled corticosteroids (ICS) with IBA and few using long-acting IBA as monotherapy. Athletes with asthma/AHR have consistently outperformed their peers, which research suggests is not due to their treatment enhancing sports performance. Research is necessary to determine how many athletes will continue to experience asthma/AHR in the years after they cease intensive endurance training.